Application of soil and water assessment tools model for runoff estimation - Hosseini, Majid; Mohd Soom, Mohd Amin; Ghafouri, Abdul Mohammed; Tabatabaei, Mahmoud Reza (Science Publications, 2011)
Problem statement: The most of the distributed or physically-based hydrologic and water quality models from developed countries are not directly applicable in developing countries due to both lack of data and different climatic conditions. Hence, there is a need for a study to be conducted a catchment of developed countries. Approach: From a review of various models to estimate runoff using a semi-distributed model, Soil and Water Assessment Tool (SWAT) was selected. Sequential Uncertainty fitting (SUFI-2), a program that is linked to SWAT was utilized for calibration and validation analysis. SUFI-2 is linked with SWAT in the Calibration Uncertainty Program known as SWAT-CUP. There are two stream gages with adequate data for calibration and validation in Taleghan basin with an area of 800 km2 in northwest of the Tehran, Iran. Joestan gauging station is located in the upstream and measures runoff from an area of 413 km2 whereas Galinak station located at the outlet of 800 km2 Taleghan catchment. Results: The results showed surface runoff was 21% of the precipitation for the upper part of the catchment and 33% at the outlet. Groundwater and lateral flows took place mostly in the mountainous upper part of the catchment with contribution of 23% and 17 %, respectively. Evapotranspiration losses at Joestan and Galinak stations were around 38% and 49% of the precipitation, respectively. Conclusion/Recommendations: This research has successfully developed a customized SWAT model by SUFI-2 program to be used by water engineers and managers in their planning of future land and water developments in Taleghan Catchment. The database system created in the study area, using dispersed datasets in GIS environment could be used not only for modeling purposes but also for decision making. High surface runoff and low interflow at Galinak station and inversely at Joestan station showed downstream of Joestan stations on need of greater soil conservation measures. The main reason is snowpack in the winter and good rangeland in other seasons. The study has produced a technique with reliable capability and high accuracy for annual and monthly water balance components of the Taleghan catchment.